Inquisitions into the complain and the non-complain customers: the Malaysian customers’ insight - Md. Zain, Osman (Centre for Promoting Ideas, 2011)
This is an inquisition study on the behaviours of Malaysian customers who complain and those who do not. Data was acquired from 214 mature working students from two Universities using two approaches. The first approach was an email-based approach that resulted in 83 returned questionnaires which accounts to 27.7 percent rate of return. The second was a self-administered approach which took place in classrooms whereby the respondents were selected randomly based on their seating. This approach resulted in 131 returned questionnaires with a 65.5 percent rate of return. The study attempts to uncover the nature of complainers and non-complainers in Malaysia and compare them with past studies from the West. The results of this study indicate that non-complain customers do exist here, and they are significantly different from those who used to complain. The complainers, as similar to that from the western studies, are more extroverted in nature as compared to the non-complainers. The findings suggest that non-complain customers from this part of the market are socially anxious, exhibit low self-efficacy, and high self-monitoring towards complaining. This paper enhanced knowledge on post-purchase perspectives from the Non-Western world represented by one of the Asian markets. The Asians, though multi-races, shared a unique culture among them that is close-knit family relationships which can either be detrimental or beneficial for marketers. The implication of this study to managers is the importance of devising a customer friendly procedure to complaining, and the importance of managing customer relationships